NORMATIVE INDICATORS OF DENTAL MANUFACTURING STEPS DURATION OF SCROLLABLE BRIDGES BASED ON PLASTIC BURNOUT ABUTMENTS AND ABUTMENTS WITH PLATFORM FOR BONDING RELYING ON IMPLANTS - E.V. Diiev; V.A. Labunets; T.V. Diieva (Ukrainian Medical Stomatological Academy, 2016)
Dental implant technology that is widely used in medical practice in Ukraine, does not have full legal status to the application, also due to the lack of standard indicators and duration of clinical dental specialists execution phases of its corresponding profile. For producing screwed prosthetic designs relying on implants many manufacturers offer plastic burnout ashfree abutments and abutments with platform for bonding on the basis of which are manufactured single crowns and bridges from cobalt-chromium alloy (CCA), cermet, metal-plastic, Metallic, all-ceramic and plastic, which could be screwed to the supporting implants with the screws. The purpose of research to establish standard indicators of the duration of manufacturing stages of screwed bridge based on plastic burnout abutments and abutments with platform for bonding relying on implants. Materials and methods The object of study the process of dental orthopedic care in the manufacture of dental screwed bridges on the basis of plastic burnout abutments and abutments with platform for bonding relying on implants. Subject of research the structure, sequence, duration and scope of the appropriate dental care, labor costs of experts. Research Methods analytical, timing, mathematical, statistical. To determine the duration of the relevant clinical and dental manipulation using officially approved by the Ministry of Health of Ukraine methodology for establishing labor dental modification by V.A. Labunets (1999). Results of the study Between the years 2010-2016 staff of the Department of Prosthetic Dentistry Institute of Dentistry of NAMS of Ukraine have been studied dental production processes of 97 different designs of screwed bridge from CCA, cermet, metal-plastic, metallic, all-ceramic and plastic-based plastic burnout abutments and abutments with platform for bonding relying on implants that were made by 36 dental technicians with different skills. During observations revealed that dental processes of manufacture of prosthesis-metal, metal-plastic, metallic and some types of all-ceramic flow over 4 laboratory stages and solid dentures, dentures pressed of unique PEEK-plastic and all-ceramic made of E-max method pressing and painting require 3 laboratory stages. The calculation of standard indicators of the duration of the laboratory stages of manufacturing screwed bridges implant according to the formula: HB screwed bridge = Tп pr.most.prot. + K opornij × Tпп one support artificial teeth + K × Tпп single artificial tooth, where: HB - standard time; Tп - fixed costs of the expert time; Tпп - variably-repeatable cost professional time; K - the number of certain structural elements of the prosthesis. Conclusions: For dental technician production stage of screwed bridges on the basis of plastic burnout abutments and abutments with platform for bonding relying on implants these indicators are as follows: 61,92- 95,47 min. - fixed costs of working time (Tп) dental appliances for the manufacture of bridges, 92,33-289,97 minutes - variable-repeatable cost of working time of dental technician to manufacture bearings bridge (CCI supports), 83,71-205,89 minutes - variable-repeatable cost of working time dental technician to manufacture artificial tooth in intermediate part of bridge prosthesis (Tпп).